A case study of consumer product company performance within global financial crisis in Malaysia / Sarah Zafirah Ibrahim - Ibrahim, Sarah Zafirah (Faculty Of Business Management, 2018)
This paper aim is to investigate the determinants that influence the firm performance on listed Consumer Product Companies within global financial crisis in Malaysia. Objective of the research, which is focusing on consumer product companies within global financial crisis based on the period of pre, during and post which is pre on 2005 and 2006, during on 2007 and 2008 and post on 2009 and 2010. The sample of this research is using the convenience 30 listed consumer product companies in Bursa Malaysia. The dependent variable is return on equity. It was measured by using profit before tax dividing with total equity. The independent variables are debt ratio, dividend yield and profitability. In determining the debt or leverage, it comes from debt ratio that measured by total liabilities divide by total asset. For measuring dividend, this research used dividend yield that comes from dividend per share divide by share price. For the profitability variable, it used gross profit margin that measuring by operating income divide by total asset. Threw out the study, the independent variable might influence the firm performance either significant or not. It will be measure by the year of 2005 until 2010. In addition, yearly data of the year period base will be used to run the information data. Panel data approach will be used to examine the relationship toward consumer product companies. For result of pre event (2005-2006), debt ratio and dividend yield have no significant relationship with return on equity, while profitability variable has a significant relationship with return on equity. For during (2007-2008), only debt ratio has a significant relationship with return on equity different with dividend yield and profitability that have no significant relationship with return on equity. Lastly, for post event (2009-2010), debt ratio and profitability have significant relationship with return on equity but dividend yield has no relationship with return on equity.